Intravenous Immunoglobulin Controls Th17 Cell-Mediated Osteoclastogenesis - Kim, Kyoung-Woon (Immune Netw, 2019)
The purpose of this study was to determine the regulatory role of intravenous Ig (IVIg) in Th17 cytokine–induced RANK ligand (RANKL) expression and osteoclast (OC) differentiation from OC precursors (pre-OC). Human CD14(+) monocytes were isolated and stimulated by Th17 cytokines (IL-17, IL-21, and IL-22) and RANKL expression was investigated using a real-time PCR. CD14(+) monocytes were incubated with RANKL, Th17 cytokines, and M-CSF, with/without IVIg, and OC differentiation was determined by counting tartrate-resistant acid phosphatase-positive multinucleated cells. OC differentiation was investigated after monocytes were cocultured with Th17 cells in the presence of IVIg. Th17 cell differentiation was determined using enzyme-linked immunosorbent assay and flow cytometry after CD4(+) T cells were cultured with IVIg under Th17 condition. Th17 cytokines stimulated monocytes to express RANKL and IVIg suppressed the Th17 cytokine-induced RANKL expression. OCs were differentiated when pre-OC were cocultured with RANKL or Th17 cytokines and IVIg reduced the osteoclastogenesis. IVIg also decreased osteoclastogenesis when pre-OC were cocultured with Th17 cells. IVIg decreased both Th17 and Th1 cell differentiation while it did not affect Treg cell differentiation. In summary, IVIg inhibited Th17 cytokine-induced RANKL expression and OC differentiation. IVIg reduced osteoclastogenesis when monocytes were cocultured with Th17 cells. IVIg also reduced Th17 polarization. IVIg could be a new therapeutic option for Th17 cell–mediated osteoclastogenesis.